O uso de recursos audiovisuais no ensino da física para educação básica - MORAES, Cleiton Miranda (2024)
The choice of this topic “Audiovisual resources in the teaching of physics for high school” is a study aimed at understanding and also reflecting on the teachinglearning process and how important the use of these resources is for the development not only of the student, but also from the teacher for accepting this challenge of using different ways to teach physics to students and showing that when it is possible to see or hear certain phenomena, we are able to capture what has been taught, as well as obtain a more mature development on experimental and philosophical issues . The school environment is not only the classroom, board and teacher, it goes beyond that, and with this perception comes the various tools used to better explain and facilitate the understanding of the subjects taught. Remembering that it is not only fixed to physics, but everything that is explained here can and should also be full-bodied in the various areas of knowledge. So we can understand that audiovisual is something that combines sound, image and reproduces an idea or exemplifies things that until then were abstract in our minds, or simply represented by words.